Organizational principles of problem-based education at the Department of Histology, Cytology and Embryology in the conditions of modern informational technologies. - Klyuchko, S. S. (Морфологія / Morphologia / Morfologìâ, 2015)
Background. Transition to the problem-based learning at the Department of Histology, Cytology and Embryology strongly requires the development of pedagogical control system, open and understandable to students. The objective of this article is to analyze the pedagogical and psychological aspects of education in terms of introduction of modern informational technologies. Methods. The data was obtained by questioning senior researchers and students of the Department of Histology, Cytology and Embryology. Results. Implementation of the test control allowed us to give an objective assessment of how students understand the connection between the theoretical material and practical actions. Undoubted advantages of the rating control are: evaluation of the individual units of work ensures the reliability of the control (test control and situational problems, diagnostics 2 microspecimens and electron micrographs). Conclusion. Detailed and phased control procedure develop students' skills of self-work, forms the experience of self-control in professional activities.